Dupilumab-Induced Lichen Planus: A Case with Oral and Cutaneous Eruptions - Laura Kern; Luisa Kleinheinrich; Robert Feldmann; Paul Sator; Alexander Stella; Friedrich Breier (Karger Publishers, 2022)
Lichen planus is a chronic, inflammatory, immune-mediated dermatosis affecting the patient's skin, scalp, mucous membranes, and nails. Drug-induced lichen planus is described after the administration of antimalarials, ß-blockers, methyldopa, NSAIDs, penicillamines, and sodium aurothiomalate. The use of biologicals such as adalimumab, etanercept, and infliximab has also been linked with the appearance of lichenoid eruptions in the recent past. In this case, we report on a patient developing oral and cutaneous lichen planus after the administration of dupilumab. The lichenoid lesions occurred after 11 months of the drug's administration and involved the buccal walls, trunk, and extremities. Dupilumab had been administered in an effort to counter severe atopic dermatitis exacerbations. Dupilumab is associated with a downregulation of T-helper 2 cell activation by blocking the Interleukin-4/Interleukin-13 pathway, so leading to a TH1/TH2 imbalance. This imbalance may cause a shift toward a TH1-mediated immune response and be an explanation for the drug-induced lichen planus. Dupilumab was discontinued, and the patient was treated with oral corticosteroids and UVB phototherapy, leading to a significant improvement in the lichen planus lesions.